The influence of inflammation on cardiovascular disease in women - Kottilil, Sita; Mathur, Poonam (Frontiers in Global Women's Health, 2022)
The onset of cardiovascular disease in women is almost a decade later than men, partly due to the protective effect of estrogen prior to menopause. Recently, it was noted that while there have been advances in improving the morbidity and mortality from CVD in women older than 55 years, the improvement in younger women has been stagnant. The mechanism behind this lag is unclear. This manuscript reviews the literature available on the sex-specific inflammatory response in the context of traditional and non-traditional cardiovascular disease risk factors. Our review suggests that women have a differential inflammatory response to various disease states that increases their risk for CVD and warrants a distinct prioritization from men when calculating cardiovascular disease risk.